Comparing Chinese youth with American youth on adjustment: An illustration of measurement issues in cross‐cultural research. (14th June 2020) - Tan, Tony Xing; Yi, Zhiyao; Li, Zhengjie; Cheng, Ke; Li, Jun
Abstract : In this article, we used results from two studies to show the need to go beyond linguistic equivalence to establish construct validity and measurement invariance in cross‐cultural research. Study 1 examined Rosenberg Self‐Esteem (RSE; 10 items) data from 156 Mainland Chinese youth ( M = 13.8 years, SD = .53) and 213 Chinese‐American youth ( M = 13.6 years, SD = 2.1) from high socioeconomic status (SES) families. The Chinese translation of the RSE has been widely used. Study 2 included 1060 Mainland Chinese youth ( M = 15.6 years, SD = 2.3) and 412 racially diverse American youth ( M = 16.0, SD = 2.9) from all SES backgrounds. Data were collected with the third and newest edition of the Behavioural Assessment System for Children‐Self Report of Personality (BASC‐3‐SRP; 189 items). We translated and back‐translated the BASC‐3‐SRP between English and Chinese to establish linguistic equivalence. All participants were females. Study 1 showed that the RSE had acceptable internal consistency but lacked construct validity. Study 2 showed that the original and the translated BASC‐3‐SRP had good internal consistency and construct validity, but nine of its 16 subscales lacked measurement invariance. These results highlight measurement issues facing international and cross‐cultural research.